PENGEMBANGAN POTENSI BAMBU SEBAGAI KERAJINAN DAN WISATA DI KAPANEWON SEMIN, GUNUNGKIDUL - Pranata, Adrianus Yoga (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
The 81st period KKN was held with the theme Society 5.0 where Atma Jaya Yogyakarta University students did not carry out work program activities directly in the field. The author is a member of KKN from group 31 who was given the responsibility to develop skills and expand knowledge in Gunungkidul district, Semin sub-district. The potential found by the author for Semin Village is in several fields. Some of them are tourism potential, agricultural potential, and artistic potential. The author also finds that Semin Village has very good bamboo potential to be developed. Therefore, the author supports the use of bamboo as a craft and tourism potential in the Semin area, Gunungkidul. By utilizing weaving techniques such as single weaving techniques, two-by-two weaving techniques, three and four braid weaving techniques, lotus weaving techniques, and clove weaving techniques, the selling value of bamboo crafts in Semin Village can increase. With good training, this weaving technique can develop the potential of bamboo that has developed in Semin Village even better.